Foreign exchange exposure and its determinants among some listed companies from selected sectors in Malaysia - Wan Nur Izni, Wan Ahmad Kamar (2015)
This study constructs an analysis on the effect of foreign exchange rate change on firm value of 90 Malaysian companies in Plantation sector, Consumer Product sector and Industrial Product sector that were listed on Bursa Malaysia for the period of January 2008 to December 2012. This study also extends the analysis by investigating the possible determinants of foreign exchange exposure. The result of this study reveals that companies in Plantation sector seems to be more exposed to foreign exchange rate risks compared to Consumer Product sector and Industrial Product sector. Besides that, size, liquidity, debt, asset turnover, profit margin, currency diversification and foreign subsidiary diversification were found to be insignificant in explaining the possible factors that can influence foreign exchange exposure. Overall, the results suggests that the extent of foreign exchange exposure was rather low with the degree of the exposure was more prominent in Plantation sector than in Consumer Product sector and Industrial Product sector. US dollar and Singapore dollar seemed to pose greater exposure on Malaysian firms though which years showed more prominent exposure was different for all the three sectors.